Developing Science Process Skills in Science Club Activities at a Private School in South Tangerang - Jessica Elfani Bermuli; Candra Yulius Tahya; Maya Puspitasari Izaak (Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
This Community Service Program (PkM) aims to develop junior high school students’ science process skills (SPS) through Science Club activities at a private school in South Tangerang, Indonesia. This activity is a collaboration between the Faculty of Education at Universitas Pelita Harapan and the private school located in the BSD area of Tangerang. Community Service Activities were held every Tuesday from January 24 to April 2024, from 3:00 p.m. to 4:30 p.m. Western Indonesian Time, and focused on assessing junior high school students' science process skills through their attendance, activities, and involvement during practical work. The method used is direct experimental learning in the laboratory to enhance students’ scientific skills. The Science Club is designed as an extracurricular platform that allows students to explore and practice concepts in Biology, Chemistry, and Physics beyond textbook learning. The program was conducted over eight sessions, where students carried out experiments on topics that are not commonly practiced in schools but can be implemented simply in the laboratory using easily accessible tools and materials. Evaluation using an SPS rubric showed positive results: 80.83% attendance and 73.33% of students achieved an A grade. In addition to improving scientific skills, the program also contributed to students’ educational, health, environmental, and psychological aspects. These results indicate the potential sustainability of the program to support holistic learning based on biblical perspectives.